Violence, Shame, and Moral Agency - An Exploration of Krista K. Thomason's Position - Henriksen, Jan-Olav (De Ethica, 2020)
Krista Thomason’s account of shame explains the link between shame and violence as something that arises out of a tension between our identity and our self-conception: those things about which we feel shame are part of our identities, but they are not part of our self-conception. She sees violence as an attempt to regain agency and control and overcome shame. Although this is an important trait in shame, to explain violence as a response to the loss of agency is not sufficient. Furthermore, it cannot explain serious self-harm as the result of shame, since such reactions undermined the agency she holds that violence attempts to reclaim. Hence, these features need to be incorporated into a wider account of shame that sees it as a response to the interruption of intentional projects and attempts for coherent agency.